Halogen-related photodissociation in atmosphere: characterisation of atomic halogen, molecular halogen, and hydrogen halide. Issue 1 (2nd January 2021) - Lin, King-Chuen; Muthiah, Balaganesh; Chang, Hsiu-Pu; Kasai, Toshio; Chang, Yuan-Pin
Abstract : Atomic halogen elimination from halogen-related compounds plays a vital role in the depletion of the ozone layer and is well investigated. However, the probabilities for elimination of molecular halogens and hydrogen halides are rarely scrutinised. We develop distinct method for the investigation of each kind of fragment. Velocity-mapping ion-imaging was employed to study the atomic halogen elimination from alkyl halides and aryl halides, focusing on the fractions of the translational energy release, the quantum yields of the atomic fragments, transition probability for curve crossing, competitive halogen-related bond fission, and anisotropy parameters to understand their dynamical complexity. Cavity ring-down absorption spectroscopy was implemented to investigate the molecular halogen fragments dissociated from the aliphatic halides and acyl halides for their optical spectra, vibrational branches, quantum yields, and the dissociation mechanisms. Time-resolved Fourier transform infrared emission spectroscopy was employed to confine the primary products of hydrogen halide elimination from acyl halides in the presence of Ar gas. It is, for the first time, to overview these existing small halogen-related fragments eliminated from halogen-containing compounds. The detailed characterisation of these fragments should unveil complicated halogen-related dissociation mechanisms which may supplement the current knowledge and help with the photochemical assessment of halogen-related environmental issue.